Simple Syntheses of New Pegylated Trehalose Derivatives as a Chemical Tool for Potential Evaluation of Cryoprotectant Effects on Cell Membrane - Pomeisl, Karel; Richter, Jan; Golan, Martin; Kratochvílová, Irena (Molecules, 2020)
In our work, we developed the synthesis of new polyfunctional pegylated trehalose derivatives and evaluated their cryoprotective effect using flow cytometry. We showed that new compounds (modified trehaloses) bound to appropriate extracellular polymeric cryoprotectants could be helpful as a chemical tool for the evaluation of their potential toxic cell membrane influences. Our aim was to form a chemical tool for the evaluation of cryoprotectant cell membrane influences, which are still not easily predicted during the freezing/thawing process. We combined two basic cryoprotectants: polyethyleneglycols (PEGs) and trehalose in the new chemical compounds-pegylated trehalose hybrids. If PEG and trehalose are chemically bound and trehalose is adsorbed on the cell surface PEGs molecules which are, due to the chemical bonding with trehalose, close to the cell surface, can remove the cell surface hydration layer which destabilizes the cell membrane. This was confirmed by the comparison of new material, PEG, trehalose, and their mixture cryoprotective capabilities.
Keywords: Trehalose; Cryopreservation; Cell Line, Tumor; Dimethyl Sulfoxide; průtoková cytometrie; Polyethylene Glycols; lidé; Freezing; Cryoprotective Agents; Flow Cytometry; kryoprezervace; polyethylenglykoly; dimethylsulfoxid; Click Chemistry; Cell Survival; zmrazování; viabilita buněk; kryoprotektivní látky; buněčná membrána; trehalosa; nádorové buněčné linie; click chemie; Cell Membrane; Humans